(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This work focuses on the planning and petroleum industry logistic and supply chains from raw materials to production distribution by developing a two-stage stochastic linear programming with recourse techniques. The paper investigates and creates a set of mathematical models which considers different parameters such as production of crude oil, transportation plan, production levels, operating conditions, production distribution plans, prices of raw materials and products under significant source of uncertainty which represent the market demand of refinery products. Expected Value of Perfect Information (EVPI) is computed a maximum amount a decision maker that should pay for additional information gives a perfect signal as to the state of nature.